Beginning gRPC with ASP.NET Core 6 : build applications using ASP.NET, Core Razor Pages, Angular and best practices in .NET 6 - Giretti, Anthony (Apress, 2022)
Broaden your developer experience by learning how to use gRPC and ASP.NET Core together on the Microsoft's developer framework, .NET 6 and discover a new way of developing APIs with gRPC. Beginning gRPC with ASP.NET Core 6 is your guide to quickly and efficiently getting down to the business of building gRPC applications in the Microsoft .NET ecosystem. Readers will dive in and build an application using gRPC and the latest technologies such Angular and ASP.NET Core Razor Pages. This book will teach you how to set up an efficient application using industry best practices such as security, monitoring, logging, and more. You will do this by performing Create, Read, Update, and Delete (CRUD) operations on a SQL Server database with Entity Framework Core. From there you will build web applications using Angular and ASP.NET Core Razor pages combined with gRPC APIs. After reading the book, you'll be able to take advantage of the full range of developer opportunities with gRPC, and come away with any understanding of which usage scenarios are best suited for your projects. And you will possess a solid understanding of the best way to build APIs with ASP.NET Core. What You Will Learn Discover the latest .NET 6 framework Benefit from a new way to design APIs Build modern web applications Migrate easily from WCF to gRPC Become comfortable with latest industry programming standards Who This Book Is For Professional developers who are interested in getting started with gRPC and want to learn how to use it to build applications in the .NET ecosystem.